(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
In the present investigation, the synthesis of few novel leads bearing 2-(p-hydroxyphenyl)-4–(substitutedphenyl)-1H-1,5–benzodiazepine pharmacophore is described. The substituted chalcone and their derivatives 3(a-j) were synthesized by base catalyzed Claisen-Schmidt condensation between p-hydroxy-acetophenone and appropriate aldehydes. The dibromostyryl ketones 4(a-j) were obtained by the reaction the chalcone with bromine in acetic acid. The dibromostyryl ketone were reacted with methanol in presence of sodium methoxide followed by acidic hydrolysis give 1-(4-hydroxyphenyl)-3-(substitutedphenyl)-1,3-propanediones. The targeted compounds; the substituted 1,5-benzodiazepines were synthesized with o-phenylenediamine and synthesized 1,3-propanediones. The structures of synthesized compounds were confirmed by spectroscopic and analytical techniques (IR, 1H-NMR, and MS). The free radical scavenging activity of the synthesized analogs was monitored by in vitro antioxidant activity protocol. The derivatives 6f, 6g, 6i, and 6j were found to exhibit good antioxidant activity with 59.07%, 41.33%, 68.3% and 60.4% scavenging activity respectively as compared to standard ascorbic acid which demonstrated 79.73% activity. The current research revealed the potential of 2-(p-hydroxyphenyl)-4–(substituted-phenyl)-1H-1,5–benzodiazepine as emerging free radical scavengers. The study helped to establish a structure-activity relationship (SAR) where the substitution on the phenyl moiety of the 1,5-benzodiazepine was found to play profound role and influence over biological activity. The research will open new avenues for the development of antioxidant moieties having perspectives in cancer, inflammation, and several other ailments.